Relation between QT duration and maximal wall thickness in familial hypertrophic cardiomyopathy. Issue 2 (1st August 2002) - Jouven, X; Hagege, A; Charron, P; Carrier, L; Dubourg, O; Langlard, J M; Aliaga, S; Bouhour, J B; Schwartz, K; Desnos, M; Komajda, M
Abstract : Background: QT abnormalities have been reported in left ventricular hypertrophy and hypertrophic cardiomyopathy. Objective: To determine the relation between left ventricular hypertrophy and increased QT interval in familial hypertrophic cardiomyopathy. Methods: The QT interval was measured in 206 genotyped adult subjects with familial hypertrophic cardiomyopathy from 15 unrelated families carrying mutations in the β myosin heavy chain (β-MHC) gene (five families, n = 68) or the cardiac myosin binding protein C (MyBPC) gene (10 families, n = 138). Subjects were classified as genetically unaffected (controls, n = 112), affected with left ventricular hypertrophy (penetrants, n = 58), or affected without left ventricular hypertrophy (non-penetrants, n = 36). Results: There was a significant increase in QTmax and QTmin from controls to non-penetrants and penetrants for both the MyBPC group (p ≤ 0.001 and p ≤ 0.001, respectively) and the β-MHC group (p ≤ 0.001 and p ≤ 0.001, respectively). In the MyBPC group, the increase in the QT interval could be explained by increased left ventricular hypertrophy. In the β-MHC group, non-penetrants had a significantly longer QTmax than controls despite the absence of left ventricular hypertrophy, and a similar QT interval to penetrants despite a lesser degree of left ventricular hypertrophy. Conclusions: In familial hypertrophic cardiomyopathy, genetically affected subjects without left ventricular hypertrophy may have a prolonged QT duration, which depends not only on the degree of left ventricular hypertrophy, when present, but also on the causative mutation.